Q-Type Spaces of Harmonic Mappings - Alaa Kamal (Journal of Mathematics)
In this paper, we attempt to investigate a new harmonic mapping class denoted by the Banach space QHp in the unit disk. Several characteristics of the class Qp are examined. We additionally describe some findings for the little QHp harmonic space, which really is a closed subspace of QHp. We also talk about the boundedness and compactness of the composition operator in the QHp space.